Financial Inclusion: A Prerequisite for Strengthening Financial Stability in Algeria - benameur, nabil (Journal of Research in Finance and Accounting, 2025)
Financial stability refers to the smooth functioning of the financial system and its ability to facilitate and support effective economic performance. It requires various factors, including sound financial institutions, stable financial markets, and efficient financial infrastructure components. According to FSAP reports issued on April 12, 2024, Algeria's financial system is characterized by a degree of stability. However, maintaining the momentum of recovery requires addressing high inflation and implementing structural reforms to promote financial inclusion, sustainable growth, and economic diversification.